COVID-19 risk behaviors in humanitarian settings: a cross-sectional study among conflict refugees in Uganda - Lawoko, Stephen; Seruwagi, Gloria; Muhangi, Denis; Ochen, Eric A.; Okot, Betty; Lugada, Eric; Masaba, Andrew; Ddamulira, Dunstan P.; Luswata, Brian; Nakidde, Catherine L.; Kaducu, Felix (International Journal Of Community Medicine And Public Health, 2021)
Background: Worldwide, behavioral change interventions are at the core of prevention efforts to contain the novel Corona Virus (COVID-19). While the evidence base to inform such interventions in the general population is growing, equivocal research in humanitarian populations is lacking. The current study describes the nature, extent and predictors of COVID-19 risk behaviors among conflict refugees in Uganda in a bid to inform prevention strategies for humanitarian settings. Methods: Cross-sectional survey data on COVID-19 risk-behaviors, demographic, socio-economic, behavioral and clinical variables was gathered from 1014 adult refugees drawn from 3 refugee settlements in Uganda, using two-staged cluster sampling. Data was analyzed using t-test, Analysis of Variance (ANOVA) and Multivariable Linear Regression. Results: Many refugees (25-70%) were involved in hygiene, congestion and nutritional/physical activity related risk behaviors likely to contribute to community transmission of COVID-19. Refugees living in rural settlements, of male sex, young age and low socio-economic status were at heightened risk of exposure to COVID-19 risk behaviors. Physical activity and healthy nutritional practices reduced the likelihood of COVID-19 risk behavior. Indulgence in COVID-19 risk behaviors increased the risk of developing COVID-19 symptoms. Conclusions: COVID-19 risk behaviors among conflict refugees in Uganda are multifaceted in nature, widespread in extent and associated with symptom development, signaling for high risk for COVID-19 transmission in humanitarian settings. The data on predictors of COVID-19 risk behaviors have unmasked underlying inequalities, holding promise for development of evidence-based interventions to meet the needs of most vulnerable clusters in the refugee community.